Design and Simulation of Carbon Steel-based Band Saw Frame - Wibowo, Heri; Sutopo; Marwanto, Arif; Ahsanul Fakhr, Ardani; Riskiyanto, Aldy (Journal of Engineering and Applied Technology, 2025)
Frame design is an important factor in ensuring optimal performance of the band saw machine due to the dynamic loads that occur during the cutting process. This study discusses the design and simulation of a band saw machine with a focus on the analysis of the strength and stability of the machine frame using carbon steel with varying thicknesses, namely 1 mm, 2 mm, and 3 mm. Simulations were performed using finite element analysis (FEA)-based software to evaluate the stress, deformation, and safety factors of each variation of steel thickness. The simulation results show that material thickness has a significant effect on the frame's ability to withstand loads. Carbon steel with a thickness of 3 mm has the best structural performance in terms of stiffness and resistance to deformation, while steel with a thickness of 1 mm shows greater deformation at the same load. Thus, choosing the right thickness is very important to ensure the efficiency and durability of the band saw machine in industrial applications.